Refined statistically modified method for load-side inertia estimation - CHEN Xinyu; WANG Chenqi; YU Chenyang; WANG Xin; XU Jianing; LI Weidong (电力工程技术, 2024)
With the development of new energy, conventional units which are the main source of system inertia are constantly being replaced. Meanwhile, the load-side inertia becomes increasingly prominent with the increase of proportion. However, the existing load-side inertia estimation method is relatively simple, and the lower estimation accuracy cannot meet the needs of system operation management. Based on the principle of inertial quantitative statistics, a refined statistically modified method for load-side inertia estimation is proposed. Starting from the inertia analysis of the load-side basic elements and inertia modelling of the basic load units, an expression of load-side inertia estimation is given under typical load operating modes. Considering the scenario of distributed power supply access with hidden effect, the expression is modified in two cases of power supply with or without inertia equipment. According to IEEE 9-bus system, a simulation system is conducted, and simulation tests are carried out respectively with behind-the-meter power supply or not. The results show that the error of load-side inertia estimation is less than 5%, which verifies the accuracy and reliability of the proposed inertia estimation method.